PERAN POSTIVE EMOTION DALAM MEMEDIASI IN-STORE PROMOTION TERHADAP IMPULSE BUYING PADA KONSUMEN GIANT EKSTRA ALAYA SAMARINDA - Indah Purnamasari; Syarifah Hudayah; Gusti Noorlitaria Achmad (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
The purpose of this study was to determine the role of positive emotion in mediating the effect of in-store promotion on impulse buying. The location is at Giant Extra Extra Samarinda. The method used in this research is quantitative method. The population in this study are consumers who have made purchases at Giant Extra Samarinda. Samples taken as many as 100 people with probability sampling method that is by utilizing snowball sampling techniques. Data collection was carried out through questionnaires. The data analysis technique used is the SEM method, namely PLS (Partial Least Square) with the help of Smart PLS software. The results showed that in-store promotion had an effect on impulse buying, in-store promotion also had an effect on positive emotion, and positive emotion had a positive effect on impulse buying. In this study also found that positive emotion mediates the effect of in-store promotion on impulse buying.